An insight into third-phase formation in the extraction of thorium nitrate by tris(2-methylbutyl) phosphate and tri-n-alkyl phosphates. Issue 6 (13th April 2019) - Sarkar, Subramee; Suresh, A.; Sivaraman, N.; Aswal, Vinod K
ABSTRACT: Third phase (TP) formation in the extraction of Th(IV) by tris(2-methylbutyl) phosphate (T2MBP) from HNO3 media was studied and compared with tri- n -butyl phosphate (TBP) systems. Concentrations of Th(IV) and HNO3 and densities of organic phases were determined as a function of Th(NO3 )4 concentration. Extractant concentrations and volume ratios in the triphasic regions were also measured. The extraction experiments show lower TP formation tendency of T2MBP. The aggregation behaviour of Th(IV) loaded solutions of tri- n -amyl phosphate (TAP), T2MBP and TBP in n -C8 D18 and n -C12 D26 were investigated using small angle neutron scattering technique and found to be in correlation with TP formation trends.